Rework causes classification model with liable parties of the contract in construction projects - Asadi, Ramin; Rotimi, James Olabode Bamidele; Wilkinson, Suzanne (Frontiers in Built Environment, 2023)
Rework is an interesting topic in the contract management of construction projects. An effective way of improving performance on construction projects is to manage rework. However, managing rework is challenging because of the dynamic nature of construction activities. A rational starting point is the identification of the root causes of rework then a framework for its management can be developed for improving construction performance. This paper reviews rework-related studies in the construction industry through a critical review of literature to investigate the main causes of rework in the construction contracts. A content analysis of the previously proposed classification methods for rework revealed that all rework causes could be grouped under various project stages. The causes of rework also could be ascribed to different project parties. However, previous studies have suggested various categories of rework, there is no commonly used classification model for rework causes in construction contracts. The current study proposes a model in three levels to address this gap. The developed model categorised rework causes in five constructs linked to three main stages of the project under two liable contract parties. The study findings show that the procurement stage has fewer categories of rework causes than design and construction. The result also reveals that the involvement level of contract parties in rework occurrence can be investigated in contract documents. Thus, this paper suggests further research in procurement stage to address rework causes in the contract conditions.